OVERCOMING DOOM SPENDING THROUGH FINANCIAL LITERACY: GENERATION Z’S PERSPERCTIVE IN ACHIEVING FINANCIAL WELL-BEING - Ihsanul Windasari Windasari; Hendra Prastya Mere Sadhu (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The phenomenon of doom spending, characterized by uncontrolled consumptive behavior in response to stress and emotional pressure, is increasingly prevalent among Generation Z. This behavior is influenced by various internal and external factors, including emotional conditions, financial constraints, social pressures, and the pervasive impact of digital media, which further encourage impulsive consumption patterns. Low financial literacy also exacerbates the tendency toward doom spending, as individuals with limited knowledge of financial management are less capable of effectively controlling their expenditures. Therefore, this study aims to analyze how Generation Z perceives doom spending, the factors influencing it, and the role of financial literacy in fostering their financial well-being. This research employs a qualitative approach through in-depth interviews with university students and young professionals who have experienced or encountered doom spending. The findings reveal that this behavior is driven by psychological stress, social media influence, and a lack of awareness regarding the importance of proper financial management. Informants with higher financial literacy levels tend to distinguish between needs and wants more effectively and adopt more rational financial strategies to avoid excessive consumption. These findings highlight the importance of more practical and experience-based financial literacy education for Generation Z. By enhancing their understanding of financial management, individuals can develop healthier financial habits and achieve long-term financial well-being. This study recommends financial education interventions through academic curricula, training programs, and increased financial awareness via digital platforms.